Synthesis, anticancer activity, toxicity evaluation and molecular docking studies of novel phenylaminopyrimidine—(thio)urea hybrids as potential kinase inhibitors. (February 2019) - Türe, Aslı; Kahraman, Deniz Cansen; Cetin-Atalay, Rengul; Helvacıoğlu, Sinem; Charehsaz, Mohammad; Küçükgüzel, İlkay
Graphical abstract: Highlights: It was aimed to design new kinase inhibitors as drug candidates. 32 new compounds with anticancer potential were designed and synthesized. Preliminary screen were performed on Huh7, MCF7 and HCT116 cell lines. Selected compounds were further investigated for mechanism and mutagenicity. Docking studies were performed to understand the binding modes of the leads. Abstract: Thirty-two novel urea/thiourea compounds as potential kinase inhibitor were designed, synthesized and evaluated for their cytotoxic activity on breast (MCF7), colon (HCT116) and liver (Huh7) cancer cell lines. Compounds10, 19 and30 possessing anticancer activity with IC50 values of0.9, 0.8 and1.6 μM respectively on Huh7 cells were selected for further studies. These hit compounds were tested against liver carcinoma panel. Real time cell electronic sensing assay was used to evaluate the effects of the compounds10, 19 and30 on the growth pattern of liver cancer cells. Apoptotic cell death and cell cycle analysis upon treatment of liver carcinoma cells with hit compounds were determined. A significant apoptotic cell death was detected upon treatment of Huh7 and Mahlavu cells with compound30 after 48 h of treatment. Additionally, compound10 caused cell cycle arrest at G0/G1 phase. Mutagenicity of hit compounds was evaluated. Assertively, these compounds were not found to be mutagenic on Salmonella typhimurium strains TA98 and TA100. To understand the binding modes of the synthesized compounds, molecular docking studies were performed using the crystal data of VEGFR and Src-kinase enzymes in correlation with anticancer activities.